Th9 Cells in Peripheral Blood Increased in Patients with Immune-Related Pancytopenia - Qing Shao; Yangyang Wang; Zhaoyun Liu; Hui Liu; Yihao Wang; Yang Zhao; Lijuan Li; Rong Fu (Journal of Immunology Research)
Background. Immune-related pancytopenia (IRP) is a kind of autoimmune disease mediated by autoantibodies in bone marrow. T helper 9 (Th9) cell is a new subset of T cell discovered recently, which mainly expresses cytokine interleukin-9 (IL-9) to exert immune function. Th9 cells are associated with a variety of inflammatory diseases, but the role of Th9 cells in IRP remains unclear. Methods. Fifty patients with IRP and 20 healthy controls were enrolled. The percentage of Th9 cells was detected by flow cytometry (FCM) and ELISA. CD4+ lymphocytes were sorted by magnetic beads, and the mRNA expression levels of Th9 cells related transcription factors PU.1 and BATF were detected by RT-PCR. Results. The percentage of Th9 cells in CD3+CD4+ cells was 2.73±1.96% in the untreated group, which was significantly higher than those in the remission group (1.21±0.86%) (p<0.01) and the control group (0.68±0.40%) (p<0.001). And that in the remission group was significantly higher than that in the control group (p<0.05). The level of IL-9 in the untreated group was 183.91±112.42 pg/mL, which was significantly higher than that in the remission group (105.96±64.79 pg/mL) (p<0.01) and control group (56.03±14.49 pg/mL) (p<0.001). That in the remission group was also significantly higher than that in the control group (p<0.01). They were negatively correlated with hemoglobin, red blood cell, white blood cell, and platelet counts and positively correlated with the percentage of CD19+B cells and CD5+CD19+/CD19+B cells, respectively. The mRNA expression levels of PU.1 and BATF in IRP patients were higher than those in controls (p<0.05). Conclusions. The percentage of Th9 cells in the peripheral blood and the level of IL-9 in the serum of patients with IRP were increased, which was related to the severity of the disease.